Comparative Study on the Cytoprotective Effects of Activated Protein C Treatment in Nonsteatotic and Steatotic Livers under Ischemia-Reperfusion Injury. (11th October 2015) - Matsuda, Akitoshi; Kuriyama, Naohisa; Kato, Hiroyuki; Tanemura, Akihiro; Murata, Yasuhiro; Azumi, Yoshinori; Kishiwada, Masashi; Mizuno, Shugo; Usui, Masanobu; Sakurai, Hiroyuki; Isaji, Shuji
Abstract : Activated protein C (APC) has cytoprotective effects on liver ischemia-reperfusion injury (IRI). However, it is unclear whether APC is beneficial in steatotic liver IRI. We compared the cytoprotective effects of APC in nonsteatotic and steatotic liver IRI. Methods. Mice fed either normal diets (ND mice) or high fat diets (HF mice), were treated with APC or saline (control) and were performed 60 min partial IRI. Moreover, primary steatotic hepatocytes were either untreated or treated with APC and then incubated with H2 O2 . Results. APC significantly reduced serum transaminase levels and the inflammatory cells infiltration compared with control at 4 h in ND mice and at 24 h in HF mice. APC inhibited sinusoidal endothelial injury in ND mice, but not in HF mice. In contrast, APC activated adenosine monophosphate-activated protein kinase (AMPK) phosphorylation in HF mice, but not in ND mice. In the in vitro study, APC significantly increased AMPK phosphorylation, ATP concentration, and survival rates of hepatocytes compared with control. Conclusion. During IRI in normal liver, APC attenuated initial damage by inhibiting inflammatory cell infiltration and sinusoidal endothelial injury, but not in steatotic liver. However, in steatotic liver, APC might attenuate late damage via activation of AMPK.